PENGARUH PERSONAL BRANDING DAN POSITIONING TERHADAP PERILAKU PEMILIH DALAM PEMILUKADA DI KABUPATEN BONEBOLANGO - M. harifin, Kurniawati (Politika: Jurnal Ilmu Politik, 2012)
ABSTRACT Post-reform era requires states to respect the freedom of individuals and groups to participate in politics. Regional head elections (Election) is a political process and who later led to the ruling on the legitimacy of the choice of the people who passed by the representatives of the people. General Election in essence aims to raise the political participation of citizens. Ironically, the political participation of citizens is often arise after mobilization undertaken by political forces through a pragmatic approach to transactional practice, so that the election be an excellent celebration of democracy that is very expensive. It is not unusual if the prospective candidate is supported by large parties, but a big problem if the prospective candidate is left of independent representatives. Swelling and financial expenses during the campaign process is definitely there, but if prospective candidates would have to form Personal branding and positioning it well then the problem will be slightly resolved. This research looks at how much the relationship between personal branding (X1) and Positioning (X2) on the behavior of voters (Y), especially for candidates who depart from an independent candidate in the Election of Bone Bolango in 2010. Note that the evaluation of Personal branding (X1) of 50.41% influence on voting behavior (Y). Furthermore Positioning (X2) gives the effect of 14.51% of the voting behavior (Y). To find out how big the contribution made by each independent variable on the dependent variable is used multiple regression. Their conclusion that there is a positive correlation between personal branding and positioning together to conduct voter registration for 0707. While the coefficient of determination (R2) obtained for 0.49 (49%) which means that the dependent variable voting behavior can be explained by the independent variables (personal branding and positioning) by 49%. While the remaining 51% is voting behavior in the community of Bone Bolango Election of 2010. Keywords: Personal branding, Positioning, Behavior of voters, Election